The arginine repressor of Escherichia coli. - Maas, W K (1994)
This review tells the story of the arginine repressor of Escherichia coli from the time of its discovery in the 1950s until the present. It describes how the research progressed through physiological, genetic, and biochemical phases and how the nature of the repressor and its interaction with its target sites were unraveled. The studies of the repression of arginine biosynthesis revealed unique features at every level of the investigations. In the early phase of the work they showed that the genes controlled by the arginine repressor were scattered over the linkage map and were not united, as in other cases, in a single operon. This led to the concept of the regulon as a physiological unit of regulation. It was also shown that different alleles of the arginine repressor could result in either inhibition of enzyme formation, as in E. coli K-12, or in stimulation of enzyme formation, as in E. coli B. Later it was shown that the arginine repressor is a hexamer, whereas other repressors of biosynthetic pathways are dimers. As a consequence the arginine repressor binds to two palindromic sites rather than to one. It was found that the arginine repressor not only acts in the repression of enzyme synthesis but also is required for the resolution of plasmid multimers to monomers, a completely unrelated function. Finally, the arginine repressor does not possess characteristic structural features seen in other prokaryotic repressors, such as a helix-turn-helix motif or an antiparallel beta-sheet motif. The unique features have sustained continuous interest in the arginine repressor and have made it a challenging subject of investigation.